Study on repetitive damage-recovery cycle of hydrophobic coating for electrowetting-on-dielectric (EWOD) applications - Youngdoo Son; Woochan Kim; Daeyoung Lee; Sang Kug Chung (Micro and Nano Systems Letters, 2024)
Abstract This study is focusing on the durability of fluoropolymer hydrophobic coatings against falling droplets. Devices such as smart self-cleaning lens or droplet-based energy generators are open-air electrowetting-on-dielectric (EWOD) devices, which are applications that utilize falling droplets. Therefore, the hydrophobic coatings of these devices are exposed to environment factors such as raindrop, and it is necessary to examine the durability of hydrophobic coatings in similar environments and the effectiveness of recovery. Thus, in this study, we simulate raindrops to damage samples with various thicknesses of Cytop (CTX-809SP2). Subsequently, damaged samples are heated to recover their hydrophobicity, and we repeat this damage-recovery cycle several times to evaluate the long-term durability of hydrophobic coating. The EWOD samples of three different hydrophobic coating thicknesses (0.1 μm, 0.5 μm, and 1.0 μm) are damaged by falling droplets from a certain height for 10 days. The damaged samples are then recovered by heating them on a hot plate at 200 ℃ for 24 h and evaluate their EWOD performance. In addition, the hydrophobic coatings are repeatedly damaged and recovered several times to examine the number of recovery limitations of the coatings. After the second damage-recovery cycle, the thickest hydrophobic coating sample shows 7 % better EWOD performance than others. Additionally, after the third damage-recovery cycle, the EWOD performance of all samples significantly degrade, experimentally verifying the number of recovery limitations of the hydrophobic coating. The results of this study are expected to provide useful information for open-air EWOD devices on the methods for evaluating their durability and the thickness selection of hydrophobic coating.